The Government Periodical Press of Western Siberia as source on personnel changes in local institutions (late XIX–early XX centuries) - V. V. Germizeeva (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the content of the official part of the newspapers «Tomsk Provincial Vedomosti», «Tobolsk Provincial Vedomosti», concerning the appointment, transfer, resignation, vacation and awards of officials of local institutions. The methodological basis of the study is the problem-chronological method, which allowed us to identify and examine in detail the possibilities of the government periodical press for studying the history of the civil service of Western Siberia in the late XIX–early XX centuries. The author draws attention to the fact that the information contained in the provincial lists is limited in comparison with the form lists. But together with archival documents and reference publications, the materials of the government periodical press allow us to fully restore the history of public service in Western Siberia, as well as to trace the terms of filling individual positions